Isomorphism Classes of Genus-2 Hyperelliptic Curves Over Finite Fields. - Encinas, L. Hernandez; Menezes, Alfred J.; Masque, J. Muñoz
We propose a reduced equation for hyperelliptic curves of genus 2 over f
Keywords: Discriminant; Hyperelliptic curves over finite fields; Public key cryptography